The Effectiveness of Time Equilibration Before Freezing in Sapera Goat Spermatozoa After Electric Separating Sperm - Saputro, Amung Logam; Prastiya, Ragil Angga; Ulinuha, Meidina Zulva; Widayani, Prasita (Jurnal Medik Veteriner, 2022)
The purpose of this study was to determine the effectiveness of time equilibration before freezing sapera goat spermatozoa after ESS (Electric Separating Sperm) on motility, viability, membrane integrity, normality and abnormality of spermatozoa. Sapera goat spermatozoa were collected using an artificial vagina and then separated using the ESS method. This study used a completely randomized formula with three treatments, which are the equilibration time of P1 (1 hour), P2 (3 hours), and P3 (4 hours), with six replications. The analysis in this study used the ANOVA test followed by the Duncan test to determine the real difference between treatments. The conclusion of this study showed the highest percentage of motility, viability, membrane integrity, normality of sapera goat spermatozoa at 1-hour treatment, for the lowest percentage of abnormalities at 1-hour treatment. Significantly different results (p <0.05) on the anode and cathode sides in all equilibration time treatments.